Study about Corporate Governance - Lamsal, Rajan; Basnet, Tikaram (Innovative Research Journal, 2023)
Nepal Rastra Bank is the highest regulatory body in all financial-related activities in Nepal. Nepal has not a long history of Corporate Governance practices. Effective corporate governance reduces ownership and control problems and draws a clear line between the shareholder and the manager. One of its major objectives is to improve the overall corporate governance system of the financial institutions including commercial banks and create financial stability in the country. Especially for the Nepalese banking sector, corporate governance practices in the commercial bank of Nepal, relationships between board size and commercial bank effects in their performance, and the relationships between audit committee size and commercial bank performance in Nepal are the objectives of the article.